Association of Husband Smoking With Wife's Hypertension Status in Over 5 Million Chinese Females Aged 20 to 49 Years. Issue 3 (March 2017) - Yang, Ying; Liu, Fangchao; Wang, Long; Li, Qian; Wang, Xingyu; Chen, Julia C.; Wang, Qiaomei; Shen, Haiping; Zhang, Yiping; Yan, Donghai; Zhang, Man; He, Yuan; et al.
Abstract : Background: The effect of second‐hand smoking, especially husband smoking, on wife's hypertension has not been well studied. The current study was aimed to assess the association of husband smoking with wife's hypertension among females aged 20 to 49 years. Methods and Results: This study included 5 027 731 females along with their husbands from the National Free Pre‐pregnancy Checkup Projects conducted across 31 provinces in China in 2014. Smoking/passive smoking status was collected by a standard questionnaire and blood pressure was measured by an electronic device after 10 minutes rest. Odds ratios and their corresponding 95% CIs for female hypertension were estimated according to smoking status of husband and wife, husbands' smoking amount, and cumulative exposure to husband smoking. Compared with neither‐smoker group, the multivariable‐adjusted odds ratio for female hypertension was 1.28 (1.27–1.30), 1.53 (1.30–1.79), and 1.50 (1.36–1.67) in husband‐only, wife‐only, and mixed group, respectively. Furthermore, a higher risk of having hypertension was associated with amount and cumulative exposure of husband smoking. For example, compared with neither‐smoker, the multivariate‐adjusted odds ratio was 1.22 (1.19–1.25), 1.24 (1.21–1.26), 1.32 (1.26–1.37), 1.37 (1.34–1.41), and 1.75 (1.64–1.87) for females whose husband smoked 1 to 5, 6 to 10, 11 to 15, 16 to 20, and ≥21 cigarettes per day, respectively ( P for trend <0.001). Subgroup analyses identified similar results. Conclusions: There were associations of husband smoking with female hypertension prevalence. A family‐based smoking restriction strategy may reduce smoking in males and improve hypertension control in females.